Purchasing Power Parities and the Size of World Economies : Results from the 2017 International Comparison Program - World Bank (Washington, DC: World Bank, 2020)
The International Comparison Program (ICP) is a worldwide statistical initiative led by the World Bank under the auspices of the United Nations Statistical Commission. It produces comparable price and volume measures of gross domestic product (GDP) and its expenditure aggregates across economies. Through a partnership with international, regional, sub-regional and national agencies, the ICP collects price data and GDP expenditures to estimate purchasing power parities (PPPs) for the world’s economies. The report provides ICP results for the benchmark year 2017 and revised results for earlier years. ICP data are used for socio-economic analyses by researchers, academics, policy makers at the national and international levels, and by organizations such as the European Union, the International Monetary Fund, the Organization for Economic Co-operation and Development, the United Nations, and the World Bank. Notably, PPPs and ICP data are used in indicators monitoring progress towards eight goals of the United Nations’ 2030 Agenda for Sustainable Development, the World Bank’s international poverty lines, and the construction of the Human Development Index by the United Nations, among others. The use of PPPs continues to grow and the ICP website (icp.worldbank.org) lists many applications of the data by the development community, academia, media and others.